Application of Marine Microbial Natural Products in Cosmetics - Ding, Jinwang; Wu, Baochuan; Chen, Liqun (Frontiers in Microbiology, 2022)
As the market size of the cosmetics industry increases, the safety and effectiveness of new products face higher requirements. The marine environment selects for species of micro-organisms with metabolic pathways and adaptation mechanisms different from those of terrestrial organisms, resulting in their natural products exhibiting unique structures, high diversity, and significant biological activities. Natural products are usually safe and non-polluting. Therefore, considerable effort has been devoted to searching for cosmetic ingredients that are effective, safe, and natural for marine micro-organisms. However, marine micro-organisms can be difficult, or impossible, to culture because of their special environmental requirements. Metagenomics technology can help to solve this problem. Moreover, using marine species to produce more green and environmentally friendly products through biotransformation has become a new choice for cosmetic manufacturers. In this study, the natural products of marine micro-organisms are reviewed and evaluated with respect to various cosmetic applications.